Analisis Kandungan Hidrokuinon pada Hand Body Lotion yang Dijual di Kecamatan Klaten Tengah dengan Metode Spektrofotometri Uv Vis - Nasikin, M. Ali; Ningrum, Ayu Dwi Retno; Rakhmayanti, Regia Desty (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2025)
Hydroquinone is a compound used as a whitening agent and to prevent pigmentation. The use of hydroquinone in hand body lotion is prohibited by BPOM because it can cause skin irritation, redness, burning sensation, bluish or blackish skin (ochronosis), cancer. This study aims to identify the content and determine the levels of hydroquinone in hand body lotion sold in Klaten Tengah District using the UV-Vis spectrophotometry method. The research method used is quantitative descriptive. The samples obtained were eight and were coded A, B, C, D, E, F, G, and H. The results showed that all samples were positive for hydroquinone with levels of 2.54%; 0.20%; 0.14%; 0.17%; 0.30%; 1.25%; 0.37%; and 2.10% so that they do not meet the requirements of BPOM RI No.23 of 2019.